2020
DOI: 10.2147/tcrm.s228880
|View full text |Cite
|
Sign up to set email alerts
|

<p>Therapeutic Potential of Ixekizumab in the Treatment of Ankylosing Spondylitis: A Review on the Emerging Clinical Data</p>

Abstract: Over the last 20 years, the greatly improved knowledges of underlying pathogenic mechanisms of AS, including the role of tumor necrosis factor (TNF), the interleukin 23/Th17 axis, and interleukin-17 (Il-17), constituted the rationale to develop biologics selectively inhibiting these pathways. For more than 10 years, anti-TNF biologics were successfully employed to treat AS, with marked improvement of signs and symptoms in around 60% of the patients. Recent knowledge of the pathophysiology of spondyloarthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The change in NE The main symptom of AS is pain, which is currently recognized as one type of IP [12]. Thus, previous studies and the development of new anti-AS medications have mainly focused on blocking inflammatory factors [13], [14], [15]. Given the large number of outpatients and lack of communication time between physicians and patients in China and the actual clinical situation in China, both physicians and patients usually pay attention to laboratory testing and imaging findings, inevitably leading to overlooking pain and other subjective symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in NE The main symptom of AS is pain, which is currently recognized as one type of IP [12]. Thus, previous studies and the development of new anti-AS medications have mainly focused on blocking inflammatory factors [13], [14], [15]. Given the large number of outpatients and lack of communication time between physicians and patients in China and the actual clinical situation in China, both physicians and patients usually pay attention to laboratory testing and imaging findings, inevitably leading to overlooking pain and other subjective symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that despite the degrees of NP, TBP and PP were significantly decreased after medication administration, PDQ was not significantly decreased (mean ± SD: 10.60 ± 6.85 vs. 9.98 ± 6.40 P = 0.0671). Subgroup analysis revealed that PDQ was decreased significantly in AS patients with PDQ [ 12 (mean ± SD: 17.06 ± 2.40 vs 15…”
mentioning
confidence: 99%
“…Moreover, elevated serum levels of IL-17 and circulating Th17 cells have been reported in AS patients. Furthermore, endogenous interactions between IL-17A and RANKL stimulate osteoclastic activity in bone, resulting in osteoporosis, bone erosions, and osteopenia in AS patients [43,49].…”
Section: Interleukin Inhibitorsmentioning
confidence: 99%
“…Notably, ustekinumab has also demonstrated good results in uveitis (37). The incidence of anterior uveitis during treatment with ixekizumab was described; however, in several cases, patients had a pre-existing history of anterior uveitis and were HLA B27 + (38).…”
Section: Ophthalmological Changesmentioning
confidence: 99%